2010
DOI: 10.1186/1476-511x-9-142
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin impairs murine melanoma growth

Abstract: BackgroundStatins induces cell cycle arrest, apoptosis, reduction of angiogenic factors, inhibition of the endothelial growth factor, impairing tissue adhesion and attenuation of the resistance mechanisms. The aim of this study was evaluate the anti-tumoral activity of simvastatin in a B16F10 melanoma-mouse model.MethodsMelanoma cells were treated with different concentrations of simvastatin and assessed by viability methods. Melanoma cells (5 × 104) were implanted in two month old C57Bl6/J mice. Around 7 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
0
18
0
2
Order By: Relevance
“…Animal experiments with the B16F10 mouse melanoma model exhibited a suppression of tumor growth by treatment with 1.6 μM simvastatin [45]. However, a regular statin treatment of patients for the control of cholesterol levels appears does not display a pronounced anti-melanoma protection [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments with the B16F10 mouse melanoma model exhibited a suppression of tumor growth by treatment with 1.6 μM simvastatin [45]. However, a regular statin treatment of patients for the control of cholesterol levels appears does not display a pronounced anti-melanoma protection [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Simvastatin was activated by dissolving in 1.8 mL of ethanol, added to 19 mL of sodium hydroxide (NaOH; 0.1 M) and then incubated for 40 minutes at 40°C to convert the lactone. To adjust the pH to 7.4, hydrochloric acid (HCl; 0.1 M) was added (8). Associations between the supernatant (S) and multiple myeloma simvastatin (Sim) were held in the proportions: 5 µL of S with 0.8 µM Sim (S1 + Sim1), 15 µL of S with 1.2 µM Sim (S2 + Sim2), 30 µL of S with 1.6 µM of Sim (S3 + Sim3), 0.8 µM of Sim with 30 µL of S (Sim1 + S3) and 5 µL of S with 1.6 µM of Sim (S1 + Sim3).…”
Section: Cell Viabilitymentioning
confidence: 99%
“…These effects have been tested in different cancers such as melanoma (Favero et al, 2010), thyroid cancer (Zhong et al, 2011) osteosarcoma (Tsubaki et al, 2011), hepatocellular carcinoma (Tijeras-Raballand et al, 2010). Additionally, several studies have shown that statins reduce cell proliferation in hematopoietic malignancies such as chronic lymphocytic leukemia (Podhorecka et al, 2010), acute promyelocytic leukemia NB4 (Sassano et al, 2007) and MM (Otsuki et al, 2004).…”
Section: Discussionmentioning
confidence: 99%